(untitled) (International Journal of Food and Nutritional Sciences, 2022)
South African racial order was distinctive among the world’s racial orders in its rifeness. Unseen and formless power had encompassed all communities based on their physical features with its heavy hand. Apartheid’s ultimate rift had been seen in socio-political, cross-cultural, ethnic and gender identities in South Africa. In this situation, South Africa’s voluminous writer, André Brink voiced the schism of apartheid in his political novel which was banned in the country. Therefore, in 1974 he translated his banned book, Kennis van die Aand, which was written in Afrikaan language into English with the title, Looking on Darkness. Brink clarifies that he tried to overcome the resistance for his book in his home country as a keen and responsible to his international audience with his translation. He began to love the process. He questioned himself about the consequences of the process. Thus this novel reflects the governmental influence on the personal lives of individuals in the country during the apartheid regime. Joseph Malan, a Coloured man, dares to love a British lady, Jessica in South Africa. He has to bear the brunt of miscegenation and objectification of his identity in his own country. This paper presents the objectification of couloured or black identity and severity of miscegenation in André Brink’s Looking on Darkness.